Contemporary oral and maxillofacial surgery - Hupp, James R.; Ellis, Edward DDS; Tucker, Myron R. (Elsevier, 2019)
One of the most respected dental surgery books in the world, Contemporary Oral and Maxillofacial Surgery, 7th Edition helps you develop skills in evaluation, diagnosis, and patient management. This comprehensive text on oral surgery procedures features full-color photographs and drawings that show how to perform basic surgical techniques, including an overview of more advanced surgical procedures and the latest developments in dental implants, instrumentation, and current technology. A detailed patient evaluation section includes guidelines on when to refer patients to specialists and how to provide supportive postoperative care. New to this edition is a chapter focusing on anesthesia in greater depth than any of the previous editions. Written by well-known OMS educators James R. Hupp, and Edward Ellis III, and Myron R. Tucker, this book is a valuable reference for dentistry and dental hygiene students alike!